CD4+ T cells in the lungs of acute sarcoidosis patients recognize an Aspergillus nidulans epitope - Greaves, Sarah A.; Ravindran, Avinash; Santos, Radleigh G.; Chen, Lan; Falta, Michael T.; Wang, Yang; Mitchell, Angela M.; Atif, Shaikh M.; Mack, Douglas G.; Tinega, Alex N.; Maier, Lisa A.; Dai, Shaodong; et al. (The Journal of experimental medicine, 2021)
Löfgren’s syndrome (LS) is an acute form of sarcoidosis characterized by a genetic association with HLA-DRB1*03 (HLA-DR3) and an accumulation of CD4+ T cells of unknown specificity in the bronchoalveolar lavage (BAL). Here, we screened related LS-specific TCRs for antigen specificity and identified a peptide derived from NAD-dependent histone deacetylase hst4 (NDPD) of Aspergillus nidulans that stimulated these CD4+ T cells in an HLA-DR3–restricted manner. Using ELISPOT analysis, a greater number of IFN-γ– and IL-2–secreting T cells in the BAL of DR3+ LS subjects compared with DR3+ control subjects was observed in response to the NDPD peptide. Finally, increased IgG antibody responses to A. nidulans NDPD were detected in the serum of DR3+ LS subjects. Thus, our findings identify a ligand for CD4+ T cells derived from the lungs of LS patients and suggest a role of A. nidulans in the etiology of LS.